Screen Adaptation of Comics and Transformation of the Cultural Context in the 1980s‑2020s - Kazyuchits, M. F (Телекинет)
The article examines the interaction of the comic book, its film adaptation and the socio-cultural context, which are aspects of the construction of the symbolic Other in the US popular culture. Using the example of the series of comics about Venom in the late 1980s‑1990s and films about Venom in the 2020s, the author identifies specific markers for these periods. A comparison of the literary basis of the Venom comics and its adaptation allows us to identify a number of motives and visual elements that indicate the influence of the 1990s film culture on the original comic. The idea of escapism is given greatest prominence here. The typical motive of a lonely hero (originating from the literary tradition of romanticism) rejected by society or even not fully accepted by superheroes is brought to its logical conclusion in the case of Venom. He is set up as an antagonist. However, the inner conflict of the hero and the popularity of the motive of a society stratified into the ordinary world of the rich and the poor, on the one hand, and the world of “invisible” people, on the other hand, finds parallels in the film culture of the 1980s and 1990s, which actively exploited a range of protest themes. The motive of the clash of Brock and Venom in the film adaptations takes on a comedic character. This indicates that in the cinema the image of Venom becomes more flexible; the understanding of the hero and the heroic has become more psychological.